Un nudo en el foco : vigilancia prospectiva del Sistema Agroalimentario Argentino 2015 - Patrouilleau, Ruben Dario; Kozel, Gabriel Andres; Lacoste, Carlos Hugo (Ediciones INTA, 2021)
Colaboradores: Lic. Marcelo Saavedra, Dr. Sergio Enrique Feingold, Dra. Roxana Blasetti, Ing. Agr. MSc. Juan Carlos Marcelino Papa, Ing. Agr. MSc. Marcelo Metzler, Dr. Marcos Yannicari, Lic. Lisandro Esteban Martínez, Lic. Ana Molnar, Lic. Leticia González